The Arabidopsis Mitochondrial Pseudouridine Synthase Homolog FCS1 Plays Critical Roles in Plant Development. (13th May 2022) - Niu, Yanli; Zheng, Yuan; Zhu, Huijie; Zhao, Hongyun; Nie, Kaili; Wang, Xiaopei; Sun, Lirong; Song, Chun-Peng
Abstract: As the most abundant RNA modification, pseudouridylation has been shown to play critical roles in Escherichia coli, yeast and humans. However, its function in plants is still unclear. Here, we characterized leaf curly and small 1 ( FCS1 ), which encodes a pseudouridine synthase in Arabidopsis. fcs1 mutants exhibited severe defects in plant growth, such as delayed development and reduced fertility, and were significantly smaller than the wild type at different developmental stages. FCS1 protein is localized in the mitochondrion. The absence of FCS1 significantly reduces pseudouridylation of mitochondrial 26S ribosomal RNA (rRNA) at the U1692 site, which sits in the peptidyl transferase center. This affection of mitochondrial 26S rRNA may lead to the disruption of mitochondrial translation in the fcs1-1 mutant, causing high accumulation of transcripts but low production of proteins. Dysfunctional mitochondria with abnormal structures were also observed in the fcs1-1 mutant. Overall, our results suggest that FCS1-mediated pseudouridylation of mitochondrial 26S rRNA is required for mitochondrial translation, which is critical for maintaining mitochondrial function and plant development.